Perancangan Game Edukasi Menggunakan Contruct 2 untuk Pembelajaran Informatika di SMAN 01 Ranah Batahan - Rosani, Junita; Musril, Hari Antoni; Derta, Sarwo; Okra, Riri (Yayasan Lembaga Studi Makwa, 2024)
One of the impacts of the implementation of the independent curriculum at SMAN 01 Ranah Batahan which requires all students to learn informatics at school, especially in class X students who have never studied informatics before. This makes students feel confused and unable to understand the learning taught by the teacher optimally. The use of monotonous learning media such as power point and printed books makes the learning atmosphere less interesting, this causes students to feel bored in following the learning process. The purpose of this research is to produce educational game learning media using the construct 2 application in informatics learning so that students are more interested in learning while playing. The research method used is the Research and Development (R&D) method with the Game Development Life Cycle (GDLC) development model. This development model consists of 6 stages, namely Initiation, PreProduction, Production, Testing, Beta and Release. The results of this study found that based on the results of product tests carried out, the validity test was obtained from three computer experts, including media, language, and material experts obtained an average validation value of 0.867, the practicality test conducted by three computer teachers obtained an average value of 0.82 and the effectiveness test was conducted on 26 students and one teacher obtained an average value of 0.91 with a high category. The impact of this research is that educational game learning media using the construc 2 application can be used by teachers and students who are able to increase the enthusiasm for learning and the level of students towards the material. Abstrak Salah satu dampak dari penerapan kurikulum merdeka di SMAN 01 Ranah Batahan yang mewajibkan seluruh siswa untuk belajar informatika di sekolah, terutama pada siswa kelas X yang sebelumnya siswa belum pernah mempelajari informatika. Hal ini membuat siswa merasa kebingunggan dan tidak mampu memahami pembelajaran yang diajarkan oleh guru secara maksimal. Penggunaan media pembelajaran yang masih monoton seperti power point dan buku cetak membuat suasana pembelajaran kurang menarik, hal ini menyebabkan siswa merasa bosan dalam mengikuti proses pembelajaran. Tujuan dari penelitian ini untuk menghasilkan media pembelajaran game edukasi menggunakan aplikasi construct 2 pada pembelajaran informatika agar siswa lebih teratrik untuk belajar sambil bermain. Metode penelitian yang digunakan yaitu metode Research and Development (R&D) dengan model pengembangan Game Development Life Cycle (GDLC). Model pengembangan ini terdiri dari 6 tahapan yaitu Inisiasi, PreProduction, Production, Testing, Beta dan Release. Hasil dari penelitian ini ditemukan bahwa berdasarkan hasil uji produk dilakukan diperoleh uji validitas dari tiga orang ahli komputer, antara lain ahli media, bahasa, dan materi diperoleh nilai rata-rata validasi sebesar 0,867, uji praktikalitas yang dilakukan oleh tiga orang guru computer diperoleh nilai rata-rata sebesar 0,82 dan uji efektivitas dilakukan terhadap 26 orang siswa dan satu orang guru diperoleh nilai rata-rata sebesar 0,91 dengan kategori tinggi. Dampak dari penelitian ini bahwa media pembelajaran game edukasi menggunakan aplikasi construc 2 dapat digunakan oleh guru dan siswa yang mampu meningkatkan semangat berlajar dan tingkat siswa terhadap materi.